The Price Dynamics of Hand Sanitizers for COVID-19 in Indonesia: Exponential and Cobweb Forms - Machmud, Amir; Minghat, Asnul Dahar Bin (Universitas Pendidikan Indonesia, 2020)
This study aims to analyze the impact of the COVID-19 pandemic on changes in handsanitizer prices in Indonesia. This study is motivated by the increasing demand for handsanitizers which has had an impact on price ratings. The method used is an explanatory survey with an exponential form approach for the demand function and Linear Cobweb Form for the supply function. The structure of the hand sanitizer market is assumed to be a perfectly competitive market. The results of the study indicate that despite changes in prices, the numerical analysis shows that prices are stable. The entry and exit of companies in the market does not affect price stability. This finding implies that after the pandemic the prices of handsanitizers will return to normal, so producers and consumers must remain rational.